Perspective for the development of aerial gymnastics in the Republic of Adygea - Redina E.S. ,; Sukmanyuk A.S. ,; Shalaya A.A. ,; Gura D.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to explore the historical and contemporary facets of the evolution of aerial gymnastics in the Republic of Adygea, we conducted a theoretical analysis and surveyed the local population. Methods and structure of the study. The results of the growth in popularity of aerial gymnastics in the republic since the first section was established in 2018 have been collected and analyzed based on information sources about the competitions held during this time. An assessment has been made of the increase in the number of sections created in the settlements of Adygea and wishing to practice aerial gymnastics based on data from sociological surveys of the republic's residents. Results and conclusions. The article explores the history of the emergence and growth of a new sport that is gaining traction in the Republic of Adygea. It delves into the origins of the sport and its potential for further development. The article also addresses the challenges of achieving full official recognition at the state level and the establishment of a unified air sports federation. These initiatives would significantly accelerate the sport's development and popularity across the country and regions. Despite initial obstacles, such as the lack of adequate training facilities, the enthusiasm of coaches and the dedication of young athletes have allowed for the first championship of the republic to be held in 2019, with international participation. The number of participants in this new discipline is growing annually. In 2023, the Republic Air Sports Federation was established.. The success of coaches and young athletes has led to an increase in the number of fans and spectators at the ongoing competitions. Based on the results of a sociological survey, a plan for the development of this sport in the communities of the republic is being created, a coaching pool is being trained, and efforts are being made to encourage children and young people to engage in sports, including aerial gymnastics.